Compromises and reorientations - Ludlow, Nicholas Piers 1968-; Gassert, Philipp 1965-; Wilkens, Andreas; Perron, Régine (Crises and compromises, 2001)
Ludlow, N. P.: The eclipse of the extremes. Demythologising the Luxembourg compromise. - S. 247-264. Gassert, P.: Personalities and the politics of European integration. Kurt Georg Kiesinger and the departure of Walter Hallstein, 1966/67. - S. 265-284. ... Wilkens, A.: L'Europe en suspens. Willy Brandt et l'orientation de la politique européenne de l'Allemagne fédérale 1966-1969. - S. 323-343. Perron, R.: Le discret projet de l'intégration monétaire européenne (1963-1969). - S. 345-367